2011
DOI: 10.1210/jc.2010-2503
|View full text |Cite
|
Sign up to set email alerts
|

Increased Estradiol and Improved Sleep, But Not Hot Flashes, Predict Enhanced Mood during the Menopausal Transition

Abstract: For women with menopause-associated depression, improvement in depression is predicted by improved sleep, and among perimenopausal women, by increasing estradiol levels. These results suggest that changes in estradiol and sleep quality, rather than hot flashes, mediate depression during the menopause transition. Therapies targeting insomnia may be valuable in treating menopause-associated depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
78
2
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 92 publications
(87 citation statements)
references
References 39 publications
4
78
2
3
Order By: Relevance
“…In fact, somatic symptoms made the strongest unique contribution to explaining depression scores, when controlling for the variance explained by the other predictors in the model. The finding that somatic symptoms were related to depressive symptoms independent of VMS is consistent with the work of others (Joffe et al, 2011;Mitchell & Woods, 1996). This is further evidence that the experience of VMS is unlikely to cause a reactive depression in most women.…”
Section: Discussionsupporting
confidence: 90%
“…In fact, somatic symptoms made the strongest unique contribution to explaining depression scores, when controlling for the variance explained by the other predictors in the model. The finding that somatic symptoms were related to depressive symptoms independent of VMS is consistent with the work of others (Joffe et al, 2011;Mitchell & Woods, 1996). This is further evidence that the experience of VMS is unlikely to cause a reactive depression in most women.…”
Section: Discussionsupporting
confidence: 90%
“…In another study, estradiol was administered to women who had depressive disorders, hot flashes and disturbed sleep in the menopause transition. Results indicated that increased estradiol levels and improved sleep quality predicted improvement in depressed mood, while reduction of hot flashes did not improve depressed mood [88]. This evidence suggested that in spite of high correlations between depressive symptoms and VMS, these variables may have distinct pathways, and hot flashes alone are not a likely cause of depression around menopause.…”
Section: Depression and Vasomotor Symptomsmentioning
confidence: 94%
“…For example, sleep problems predicted next-day negative mood, but an association with vasomotor symptoms was found only in women who had depression at the study baseline [96]. In an intervention study of women who had depressive disorders, increasing levels of estradiol and improved sleep quality predicted improvement in depressed mood in perimenopausal women, but improved hot flashes did not improve depressed mood [88]. The researchers concluded that changes in estradiol and sleep quality, rather than hot flashes, may mediate depression during the menopause transition.…”
Section: Depression and Poor Sleepmentioning
confidence: 99%
“…The third study, a recent double-blind RCT [27] aimed at examining the role of sleep disturbance in the etiology of menopausal depression, compared the efficacy of 8 weeks of transdermal 17-β estradiol (0.05 mg/day), the hypnotic zolpidem (10 mg/day), and placebo. It included 72 peri-and postmenopausal women aged 40-60 meeting DSM-IV criteria for a unipolar depressive disorder of mild to moderate severity as well as meeting threshold criteria for an insomnia syndrome.…”
Section: The Perimenopause and Early Postmenopausementioning
confidence: 99%